Initiation of minus-strand RNA synthesis by the brome mosaicvirus RNA-dependent RNA polymerase: use of oligoribonucleotide primers. - Kao, C C (1996)
Various DNA- and RNA-dependent RNA polymerases have been reported to use oligoribonucleotide primers to initiate nucleic acid synthesis. For the brome mosaic virus RNA-dependent RNA polymerase (RdRp), we determined that in reactions performed with limited GTP concentrations, minus-strand RNA synthesis can be stimulated by the inclusion of guanosine monophosphate or specific oligoribonucleotides. Furthermore, guanylyl-3',5'-guanosine (GpG) was incorporated into minus-strand RNA and increased the rate of minus-strand RNA synthesis. In the presence of GpG, RdRp's Km for GTP decreased from 50 microM to approximately 3 microM while the Kms for other nucleotides were unaffected. These results have implications for the mechanism of initiation by RdRp.